2015
DOI: 10.1152/ajpcell.00289.2014
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of NHE8 expression impairs Leydig cell function in the testes

Abstract: Multiple sodium/hydrogen exchanger (NHE) isoforms are expressed in the testes, and they play various roles in cell volume regulation, intracellular pH regulation, and fluid absorption. NHE8, the most recently characterized NHE family member, is detected in the Leydig cells in humans and mice in great abundance by immunohistochemistry in the current study. Male mice lacking NHE8 expression were infertile. Despite having intact male reproductive organs, male NHE8 Ϫ/Ϫ mice have smaller testes and lacked spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 45 publications
(64 reference statements)
2
33
0
Order By: Relevance
“…Ϫ/Ϫ mice never produced progeny, as reported previously (26,30). Vaginal plugs observed in breedings with male Nhe8 Ϫ/Ϫ mice indicated normal mating behavior, libido, copulation, and ejaculation.…”
Section: Disruption Of Nhe8 Causes Male Infertility In Micesupporting
confidence: 82%
See 3 more Smart Citations
“…Ϫ/Ϫ mice never produced progeny, as reported previously (26,30). Vaginal plugs observed in breedings with male Nhe8 Ϫ/Ϫ mice indicated normal mating behavior, libido, copulation, and ejaculation.…”
Section: Disruption Of Nhe8 Causes Male Infertility In Micesupporting
confidence: 82%
“…Although we unambiguously identified a germ cell-intrinsic defect in acrosome formation as underlying the male infertility of Nhe8 Ϫ/Ϫ mice, Xu et al (30) recently suggested that it is caused by reduced testosterone levels stemming from impaired trafficking of the luteinizing hormone receptor in Leydig cells.…”
Section: Loss Of Nhe8 Disrupts Acrosome Formation In Micementioning
confidence: 57%
See 2 more Smart Citations
“…Several isoforms of NHE have been demonstrated to play a role in male reproduction. For example, disruption of NHE8 expression could result in impaired Leydig cell function and smaller testes, as well as fewer spermatozoa [11]. Interestingly, three NHEs have been identified in spermatozoa, namely NHE1, NHE5, and NHE10 (spermspecific NHE isoform, sNHE) [12,13].…”
Section: Introductionmentioning
confidence: 99%